2013
DOI: 10.5625/lar.2013.29.3.178
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of a β-dunnione compound MB12662 on gastric secretion and ulcers

Abstract: The effects of a β-dunnione compound MB12662 on the gastric secretion and ulcers were investigated in rats. In order to assess the effects of MB12662 on the gastric secretion and acidity, rats were subjected to pylorus ligation operation, and 6 hours later, gastric fluid was collected. Treatment with MB12662 reduced the gastric fluid volume to 47.3% of control level and increased pH. In an alcohol-induced ulcer model, rats were orally administered 3 mL/kg of ethanol, and 1 hour later, the ulcer lesions ware me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Such an efficacy of MB12662 might be due to its intestine-preserving activity which lowers ensuing retching and vomiting, prevents dehydration and inability of food consumption, and recovers animals as demonstrated in mice. The protective effects of MB12662 on gastric ulcers induced by alcohol and stress were also confirmed in rats ( Jo et al ., 2013 ). Since radiotherapy also induces intestinal injury and emesis as in chemotherapy ( Priestman et al ., 1990 ; Farrell et al ., 1998 ; Jo et al ., 2000 ), it is expected that MB12662 would be effective for the relief of radiation-induced gastrointestinal problems.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Such an efficacy of MB12662 might be due to its intestine-preserving activity which lowers ensuing retching and vomiting, prevents dehydration and inability of food consumption, and recovers animals as demonstrated in mice. The protective effects of MB12662 on gastric ulcers induced by alcohol and stress were also confirmed in rats ( Jo et al ., 2013 ). Since radiotherapy also induces intestinal injury and emesis as in chemotherapy ( Priestman et al ., 1990 ; Farrell et al ., 1998 ; Jo et al ., 2000 ), it is expected that MB12662 would be effective for the relief of radiation-induced gastrointestinal problems.…”
Section: Discussionmentioning
confidence: 67%
“…In general, anti-cancer agents exert their cytotoxicity via DNA alkylation as well as radical reactions ( Husain et al ., 1998 ; De Martinis and Bianchi, 2001 ; Jeong et al ., 2005 ; Lee et al ., 2008 ). Interestingly, MB12662 and its derivative MB12066 (β-lapachone; 3,4-dihydro-2,2-dimethyl-2H-naphthol[1,2-β]pyran-5,6-dione) markedly reduced gastric secretion and prevented alcoholic gastric ulcers accompanied by oxidative tissue damage ( Park et al ., 2011 ; Jo et al ., 2013 ). In spite of anti-oxidative, anti-gastrosecretory, and anti-ulcer activities, it is believed that the major action mechanism of MB12662 might be its NAD + -preserving potential ( Hwang et al ., 2009 ), based on the much higher efficacy in alcoholic ulcers than in stress-induced ulcers ( Jo et al ., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, pyloric ligation was performed to induce damage to the stomach wall through the retention of gastric acids (Jo et al, 2013). This procedure is essential and can reveal possible changes in parameters related to the gastric contents (Barros et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, intracellular NAD + /NADH ratio can be easily controlled by NQO1 that carry out redox reactions by transferring electrons from NADH to its substrates [19,42,43]. Recently, it has been reported that an increase in the NAD + /NADH ratio by dunnione, an analog of β-lapachone (a well-known NQO1 substrate), shows beneficial effects on various metabolic syndromes [44], alcoholic ulcers [45], and acute pancreatitis [28].…”
Section: Discussionmentioning
confidence: 99%